O desenvolvimento diferenciado na escola: um estudo sobre a inclusão escolar de uma criança com transtorno do espectro autista - Araujo, Camila Azevedo de [UNIFESP] (2014)
This work addresses aspects of the process of school inclusion of children with Autism Spectrum Disorder (ASD). The work is based on the historical-cultural psychology, with emphasis on the ideas of Lev Vigotski about the social dimension of development of people with disabilities and the importance given to education in this process. The research articulates the interview and participant observation in constructing a case study of school inclusion of a child with ASD in early childhood education school in Sao Paulo in order to understand how the process of the school inclusion of the child occurs, whether and how this process impacts in her development in relation to the defining characteristics of the disorder, related to language and social interaction. This analysis revealed that the conditions and embodiments of the process of school inclusion in the context of early childhood education are organized around the different behaviors displayed by children. At school, these behaviors, deemed as inadequate and resulting from disorders are influenced by prevailing conceptions of ASD, related to the existence of this diagnosis. Stands out in the analysis, the need to understand and discuss the role played by these conceptions and by the action of the school environment (teachers, children and forms of organization of school work) in the emergence of language’s possibilities of participation of children in school practices and school inclusion.